Kedudukan Jabatan Fungsional Perancang Peraturan Perundang-Undangan dalam Perspektif Penyederhanaan Birokrasi - Isnandar Aristo Prabowo; Hedwig Adianto Mau; Mardi Candra (Syntax Idea)
Harmonization is a process of harmonizing the substance and technique of drafting laws and regulations. Within the framework of the national legal system, follow-up harmonization is regulated in Permenkumham Number 22 of 2018 and Permenkumham Number 23 of 2018. The method used in this study is normative legal research. The research data comes from primary legal materials, secondary legal materials and tertiary legal materials which are collected through library techniques. The analysis of legal material used in this study is by means of legal interpretation (interpretation) and legal construction methods. From the research results it can be obtained that explicitly, the positions of drafters and drafters of legislation in the formation of laws and regulations according to Permenkumham Number 23 of 2018 are contained in Article 3 paragraph (1) and (2) which explains that the designer has the task of preparing, formulate and process draft laws and regulations and other legal instruments and in implementing this matter the designer of laws and regulations must carry out harmonization, and must attach a letter of completion of harmonization, and the designer has an important role, because the designer must be able to create regulations that are in harmony with existing regulations . In addition, the designer must also be able to make regulations whose contents do not give rise to dubious interpretations. In the stages of drafting regulations, the designer always plays an important role in each stage. In the formation of regional regulations, the designer is always present at every stage of formation.